Endurance training significantly increases serum endocan but not osteoprotegerin levels: a prospective observational study. Issue 1 (December 2017) - Sponder, Michael; Campean, Ioana-Alexandra; Emich, Michael; Fritzer-Szekeres, Monika; Litschauer, Brigitte; Bergler-Klein, Jutta; Graf, Senta; Strametz-Juranek, Jeanette
Abstracts Background Endocan (EN) was suggested a potential inflammatory and cardiovascular disease (CVD) marker which might also be involved in renal failure and/or renal failure-associated vascular events. It is not clear whether osteoprotegerin (OPG) is a pro- or anti-atherogenic factor, however, it is agreed upon that OPG is elevated in subjects with increased calcification status. The aim of the study was to investigate the influence of long-term physical activity on serum endocan (EN) and osteoprotegerin-levels. Methods One hundred nine subjects were told to increase their amount of physical activity for 8 months by performing 150min/week moderate or 75min/week vigorous exercise. Incremental cycle ergometer tests were performed at the beginning and the end of the study to prove and quantify the performance gain. Blood samples were drawn at baseline and every 2 months for the determination of EN and OPG. To investigate the difference between baseline and 8 months levels of EN and OPG we used a paired samplet -test. To investigate the significance of the tendency of the progression (baseline/2 months/4 months/6 months/8 months) we used a Friedman test. Results Thirty-eight female and 60 male subjects completed the study. In the group of 61 subjects who had a performance gain by >4, 9% EN-levels increased from 146 ± 110 to 196 ± 238 pg/ml (p = 0, 036) equivalent to an increase of 33, 5% but there was no significant change in OPG (4, 4 ± 2, 4 pmol/l vs. 4, 3 ± 2, 1 pmol/l;p = 0, 668). Conclusions Physical activity increases significantly EN-levels relativizing the status of EN as proinflammatory factor. EN should rather be considered as a mediator which is involved in several physiological (e.g., angiogenesis) but also pathological processes (e.g., CVD, tumour progression or endothelium-dependent inflammation) and whose expression can be significantly influenced by long term endurance training. Trial registration Clinical trial registration number:NCT02097199 Date of trial registration at Clinical Trials.gov: 24.03.2014; last update: 6.1.2016